Changes in food and nutrition security in Malawi: Analysis of recent survey evidence - Verduzco-Gallo, Íñigo; Ecker, Olivier; Pauw, Karl (International Food Policy Research Institute, 2014)
A large proportion of Malawian households are caught in a trap where poverty and food insecurity reinforce one another and where periods of food deficits and severe food crises are frequent occurrences. In recognition of this, the Malawian government has since 2005/06 implemented a large-scale Farm Input Subsidy Program (FISP), which supplies half of smallholder farmers with sufficient fertilizer and maize seeds to satisfy the maize consumption needs of an average-sized family. While the program boosted maize production and lowered maize prices, thus ensuring increased caloric availability at the household level, its effect on overall food consumption, dietary diversity, micronutrient deficiency, and child nutrition is less clear. This study evaluates household expenditure survey data to measure changes in nutrition outcomes between 2004/05 and 2010/11.